Jaminan Mutu Pendidikan Guru - Subardi Subardi (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
The face of the world of education in the country still faces various problems, such as the low level of equity in getting education, the low quality and relevance of education, the weak management of education, and the lack of budget allocations in education. Associated with the low quality of education is closely related to the still low competence and professionalism of teachers. To improve the quality of teachers, there is a need for policies to improve the quality of teacher education, including increasing the level of education S1 / S2 / S3 and the equalization program. In addition, there is a need for certification to improve teacher professionalism, for example PKG (Teacher Activity Center), and KKG (Teacher Working Group), Educational Workforce Training Institute (LPTK) and Teachers Association of the Republic of Indonesia (PGRI). Increasing the quality of teacher competence will in turn improve the quality of education itself. Abstrak Wajah dunia pendidikan di tanah air masih menghadapi berbagai permasalahan, seperti rendahnya pemerataan memperoleh pendidikan, rendahnya kualitas dan relevansi pendidikan, lemahnya manajemen pendidikan, dan minimnya alokasi anggaran bidang pendidikan. Berkaitan dengan rendahnya kualitas pendidikan sangat terkait dengan masih rendahnya kompetensi dan profesionalitas guru. Untuk meningkatkan mutu guru perlu adanya kebijakan meningkatkan mutu pendidikan guru, di antaranya meningkatkan jenjang pendidikan S1/S2/S3 dan program penyetaraan. Selain itu, perlu adanya sertifikasi untuk meningkatkan profesionalisme guru, misalnya PKG (Pusat Kegiatan Guru), dan KKG (Kelompok Kerja Guru), Lembaga Pelatihan Tenaga Kependidikan (LPTK) dan Persatuan Guru Republik Indonesia (PGRI). Meningkatnya kualitas kompetensi guru pada gilirannya akan meningkatkan kualitas pendidikan itu sendiri.